2017
DOI: 10.1021/acs.jafc.7b02809
|View full text |Cite
|
Sign up to set email alerts
|

Selenomethionine as a Safer Substitute for Barium Selenate in Long-Acting Injectable Se Supplements for Food-Producing Animals

Abstract: Nutritional supplementation with selenium (Se) can prevent Se deficiency in food-producing animals. Injection with slow-release formulations is a preferred method for free-range grazing sheep and cattle, and barium selenate (BaSeO) provides optimal efficacy. This chemical can become a health risk to humans if the concentrated depot of an injection site is consumed, and consequently such use is recently banned in the EU. A possible replacement is selenomethionine (SeMet), a naturally occurring form of Se supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…7,11) SeMet is considered a useful chemical form for nutritional supplementation compared with inorganic selenium compounds. [12][13][14][15] Some studies have reported that patients with asthma showed significantly lower selenium concentration in nails or blood and significantly lower GPx activity in the blood. [16][17][18][19][20] According to a cohort study on AD prevention, selenium deficiency has been reported to increase the risk of AD.…”
mentioning
confidence: 99%
“…7,11) SeMet is considered a useful chemical form for nutritional supplementation compared with inorganic selenium compounds. [12][13][14][15] Some studies have reported that patients with asthma showed significantly lower selenium concentration in nails or blood and significantly lower GPx activity in the blood. [16][17][18][19][20] According to a cohort study on AD prevention, selenium deficiency has been reported to increase the risk of AD.…”
mentioning
confidence: 99%